Tissue-Specific Expression of DNA Methyltransferases Involved in Early-Life Nutritional Stress of Chicken, Gallus gallus - Kang, Seong W.; Madkour, Mahmoud; Kuenzel, Wayne J. (Frontiers in Genetics, 2017)
DNA methylation was reported as a possible stress-adaptation mechanism involved in the transcriptional regulation of stress responsive genes. Limited data are available on effects of psychological stress and early-life nutritional stress on DNA methylation regulators [DNMTs: DNA (cytosine-5)-methyltransferase 1 (DNMT1), DNMT1 associated protein (DMAP1), DNMT 3 alpha (DNMT3A) and beta (DNMT3B)] in avian species. The objectives of this study were to: (1) investigate changes in expression of DNMT1, DMAP1, DNMT3A, and DNMT3B following acute (AS) or chronic immobilization stress (CS); (2) test immediate effect of early-life nutritional stress [food deprivation (FD) for 12 h (12hFD) or 36 h (36hFD) at the post-hatching period] on expression of DNA methylation regulators and glucocorticoid receptor (GR), and the long-term effect of early-life nutritional stress at 6 weeks of age. Expression of DNMTs and plasma corticosterone (CORT) concentration decreased by CS compared to AS (p < 0.05), indicating differential roles of DNA methylation regulators in the stress response. Plasma CORT at 12hFD and 36hFD birds increased compared to control birds (12hF and 36hF), but there were no significant differences in plasma CORT of 12hFD and 36hFD birds at 6 weeks of age compared to 6 week controls. DNMT1, DMAP1, and DNMT3B expression in the anterior pituitary increased by 12hFD, but decreased at 36hFD compared to their controls (P < 0.05). In liver, DNMT1, DNMT3A, and DNMT3B expression decreased by 12hFD, however, no significant changes occurred at 36hFD. Expression of DMAP1, DNMT3A, and DNMT3B in anterior pituitary and DMAP1 and DNMT3A expression in liver at 6 weeks of age were higher in 36hFD stressed birds compared to controls as well as 12hFD stressed birds. Hepatic GR expression decreased by 12hFD and increased by 36hFD (p < 0.05). Expression patterns of GR in the liver of FD stress-induced birds persisted until 6 weeks of age, suggesting the possible lifelong involvement of liver GR in early-life nutritional stress response of birds. Taken together, results suggest that DNA methylation regulator genes are tissue-specifically responsive to acute and chronic stress, and hepatic GR may play a critical role in regulating the early-life nutritional stress response of birds. In addition, the downregulation of DNMT1 and DMAP1 may be one of the adaptive mechanisms to chronic early-life nutritional stress via passive demethylation.